2007
DOI: 10.1016/j.cardiores.2006.10.021
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibition with perindopril and endothelial function. Results of a substudy of the EUROPA study: PERTINENT

Abstract: Abnormal endothelial function occurs in patients with coronary artery disease, and this can be counteracted by angiotensin-converting enzyme inhibition with perindopril. These effects could contribute, at least in part, to explaining the results of the main EUROPA Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 33 publications
3
57
0
13
Order By: Relevance
“…53,54 In the PERTINENT study, perindopril also improved the endothelial function, and specifically decreased vWf levels. 55 This study extends this observation to demonstrate that ACE inhibition decreases acute endothelial injury during dialysis.…”
Section: Discussionsupporting
confidence: 67%
“…53,54 In the PERTINENT study, perindopril also improved the endothelial function, and specifically decreased vWf levels. 55 This study extends this observation to demonstrate that ACE inhibition decreases acute endothelial injury during dialysis.…”
Section: Discussionsupporting
confidence: 67%
“…In a subanalysis of the recent EUROPA study (examining the beneficial effects of ACE-inhibition in patients with stable coronary artery disease), perindopril appeared to increase expression and activity of eNOS by 19% and 27% respectively, as well as a significant reduction in plasma levels of angiotensin II, tumour necrosis factor-α and an increase in bradykinin, nitrate and nitrite 82 .…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 98%
“…14 The Perindopril Dysfunction and Neurohormonal Activation Trail, a substudy of the EUROPA trial, has shown that perindopril reduces the rate of endothelial apoptosis. 15 Increased myocyte apoptosis is an important biological component of remodeling, particularly in elderly patients. All of these hypotheses are being explored in predefined sub-studies of PREAMI.…”
Section: Discussionmentioning
confidence: 99%